Factors influencing Malaysian driversâ€™ tendency on underreporting - Sarah Nik Zamri, Nik; Hasanah Zamzuri, Zamira; Ibrahim, Kamarulzaman (International Journal of Engineering and Technology, 2019)
The reported accidents data on sites is essential to measure the effectiveness of any road safety policy. If an accident remains unreported, the vital information about the characteristics of the accident will be lost. The choice of appropriate safety measures may, in turn, be adversely affected by the loss of the data. This current study is aimed to determine the reasons for the underreporting of accidents in Malaysia. Random samples comprising 2000 individuals were interviewed in person and data on their demographic background and experience involved in accidents were recorded. Out of 1422 accidents, 662 accidents were recorded as unreported accidents. The findings indicate that in general, Malays aged between 60 and 69, living in rural area, who are single and are motorcyclists tend not to report the accidents.Â Â